Alleviating extreme poverty in Chile: The short term effects of Chile Solidario - Emanuela Galasso (Estudios de Economía, 2011)
This paper evaluates the effect of an anti-poverty program, Chile Solidario, during its first two years of operation. We find that the program tends to increases significantly their take-up of cash assistance programs and of social programs for housing and employment, and to improve education and health outcomes for participating households. There is no evidence that the participation to employment program translates into improved employment or income outcomes in the short term. Finally, we provide suggestive evidence of the key role that the psycho-social support had in enabling this change, by increasing awareness of social services in the community as well as households' orientation towards the future.
Keywords: C14; C51; I31; I38; O15; 330; program evaluation; matching estimators; extreme poverty; Chile; Armut; Armutspolitik; Chile